RETRACTED: Aldawsari et al. Gum Acacia Functionalized Colloidal Gold Nanoparticles of Letrozole as Biocompatible Drug Delivery Carrier for Treatment of Breast Cancer. Pharmaceutics 2021, 13, 1554 - Hibah M. Aldawsari; Sima Singh; Nabil A. Alhakamy; Rana B. Bakhaidar; Abdulrahman A. Halwani; Shaimaa M. Badr-Eldin (MDPI AG, 2024)
The Pharmaceutics Editorial Office retracts the article, "Gum Acacia Functionalized Colloidal Gold Nanoparticles of Letrozole as Biocompatible Drug Delivery Carrier for Treatment of Breast Cancer" [...]